Cost effectiveness of surveillance for GI cancers - Omidvari, A.; Meester, R.; Lansdorp_Vogelaar, Iris (2016)
Gastrointestinal (GI) diseases are among the leading causes of death in the world. To reduce the burden of GI diseases, surveillance is recommended for some diseases, including for patients with inflammatory bowel diseases, Barrett's oesophagus, precancerous gastric lesions, colorectal adenoma, and pancreatic neoplasms. This review aims to provide an overview of the evidence on cost-effectiveness of surveillance of individuals with GI conditions predisposing them to cancer, specifically focussing on the aforementioned conditions. We searched the literature and reviewed 21 studies. Despite heterogeneity of studies in terms of settings, study populations, surveillance strategies and outcomes, most reviewed studies suggested at least some surveillance of patients with these GI conditions to be cost-effective. For some high-risk conditions frequent surveillance with 3-month intervals was warranted, while for other conditions, surveillance may only be cost-effective every 10 years. Further studies based on more robust effectiveness evidence are needed to inform and optimise surveillance programmes for GI cancers.